The VP7 Genes of Two G9 Rotaviruses Isolated in 1980 from Diarrheal Stool Samples Collected in Washington, DC, Are Unique Molecularly and Serotypically - Cao, Dianjun (American Society for Microbiology (ASM), 2008)
In a retrospective study of archival diarrheal stool samples collected from 1974 to 1991 at Children's Hospital National Medical Center, Washington, DC, we detected three genotype G9P[8] viruses in specimens collected in 1980, which represented the earliest human G9 viruses ever isolated. The VP7 genes of two culture-adapted 1980 G9 viruses were phylogenetically related closely to the lineage 2 G9 virus VP7 gene. Unexpectedly, however, the VP7s of the 1980 G9 viruses were more closely related serotypically to lineage 3 VP7s than to lineage 2 VP7, which may be supported by amino acid sequence analyses of the VP7 proteins.